MediaLab: video as a multi-valent tool for science teaching and learning. Issue 1 (2nd January 2021) - Potter, Martin; Tuck, Kellie L.; Robinson, Andrea J.; Richardson, Paul W.; Grieve, Anna
ABSTRACT: In this article we examine the utility of video storytelling in the discipline of food chemistry in the development of media literacy for science graduates and as a radical approach to science teaching and learning where the production of a video is both a process and a product. The pedagogical programme aimed to integrate food chemistry and digital video technology using an iPhone. Students, in groups of four, prepared a four-minute video that demonstrated their knowledge of food chemistry either by preparation of a food item, or by visiting a local industry body and were charged with describing and videoing the food chemistry process they observed. As part of this programme students were taught videography skills by filmmakers and mentored by chemistry educators to ensure that the food chemistry described was comprehensive and accurate. This programme facilitated a learning environment in which students could construct, develop, learn, and consider their understanding through multiple sensory inputs. The programme fostered connections between research and education, allowed more personalised learning to develop, and permitted alternate assessment strategies.